2005
DOI: 10.1002/cm.20084
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of axonemal outer dynein arms in situ by electron tomography

Abstract: We present here for the first time a 3D reconstruction of in situ axonemal outer dynein arms. This reconstruction has been obtained by electron tomography applied to a series of tilted images collected from metal replicas of rapidly frozen, cryofractured, and metal-replicated sperm axonemes of the cecidomid dipteran Monarthropalpus flavus. This peculiar axonemal model consists of several microtubular laminae that proved to be particularly suitable for this type of analysis. These laminae are sufficiently plana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…These results predict that any movement of the stalk or tail will also contain a nonplanar component. A nonplanar bending of the stalk is in agreement with static in situ tomography studies, where stalks are shown to lie obliquely with respect to the dynein ring (27). Moreover, this observation suggests that previous 2D electron micrograph images in which the molecule is forced to lie flat on the substrate might not accurately capture the conformational changes that occur during force generation (27).…”
Section: ; See Si Text For Details)supporting
confidence: 83%
“…These results predict that any movement of the stalk or tail will also contain a nonplanar component. A nonplanar bending of the stalk is in agreement with static in situ tomography studies, where stalks are shown to lie obliquely with respect to the dynein ring (27). Moreover, this observation suggests that previous 2D electron micrograph images in which the molecule is forced to lie flat on the substrate might not accurately capture the conformational changes that occur during force generation (27).…”
Section: ; See Si Text For Details)supporting
confidence: 83%
“…This extension shares the same location as the interface between the outer and inner dynein arms in earlier work, 35 suggesting that bulb 1 is this interface. The top plate, which is assigned as the α-ring (see the next section), is connected to the rest of the outer dynein arm almost exclusively through the slender rod, whereas the middle and the bottom plates have a few direct The stalks that were visualized in freeze-fractured replicas 27,33 are not visible in our tomograms. This is probably because the coiled-coil stalks are too thin (20 Å) for the current resolution, and the variation of the stalk angles in rigor smeared the structure by averaging.…”
Section: Overall Feature Of the Outer Dynein Armmentioning
confidence: 71%
“…The quick-freeze, deep-etch technique, 4,27,29,30 the negative staining technique, 31,32 and electron tomography [33][34][35] applied to dynein arms in situ showed that head domains stack on the microtubule doublet and that there are links between the neighboring arms. In particular, the three-dimensional structure of wildtype Chlamydomonas flagella reconstructed by electron cryo-tomography and single-particle averaging 35 supported the idea that the AAA rings of the α, β and γ-heavy chains stack on the A-microtubule.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy of dynein shows a ⌽-shaped structure, indicating that the tails of the two heads are close to each other and the ring domains partially overlap (10,25). When the heads of dynein bind to the microtubule, they also overlap (25)(26)(27). A possible model to explain the stepping movement is that the dynein heads are positioned axially along the microtubule similar to kinesin.…”
Section: Discussionmentioning
confidence: 99%